2018
DOI: 10.21608/epsj.2018.17108
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Immunological Performance of Domyati Ducklings Fed Different Levels of Coconut Oil

Abstract: This study aimed to determine the effect of dietary supplementation of coconut oil levels on some physiological and immunological responses in ducklings during growing period (28-89 day of age). A total number of 120 Domyati ducklings, 28-day old were used, weighted 530-545 g and divided into four experimental groups, each of three replicates to determine the effects of feeding diets contained different levels of coconut oil (CO) as a medium chain fatty acids (MCFA) source. The experimental groups were arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, El-Abasy et al 21 suggested that including dietary coconut (2%) in rabbit diets may have a positive impact on the animals' health and immunological functions. With the same trend, El Kholy et al 31 found that dietary supplementation of 1.5 or 2% of coconut oil in Domyati ducklings diets increased plasma immunoglobulin levels, which collectively suggested that the immunological response had improved. The non- significant effect of coconut oil as immune stimulator in our study may be due to unstressed condition that birds reared in.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, El-Abasy et al 21 suggested that including dietary coconut (2%) in rabbit diets may have a positive impact on the animals' health and immunological functions. With the same trend, El Kholy et al 31 found that dietary supplementation of 1.5 or 2% of coconut oil in Domyati ducklings diets increased plasma immunoglobulin levels, which collectively suggested that the immunological response had improved. The non- significant effect of coconut oil as immune stimulator in our study may be due to unstressed condition that birds reared in.…”
Section: Discussionmentioning
confidence: 83%
“…Upgrading the capacity of immunity to resist the illnesses of livestock without antibiotics would not as it were advantage the animal's health, welfare and productivity but it is additionally a vital strategy in endeavors to make strides the microbiological security of poultry products (Sejian et al, 2011;El-Kholy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%